(untitled) (Innovative professional education, 2025)
The legislative support for vocational education in Austria was studied. The formation of the Austrian system of quality assurance for vocational education took place in accordance with the European integration processes of VET in the EU. The launch of the «VET quality initiative – QIBB» in 2004 was a significant step towards quality assurance in the VET system in Austria. From the 2021-2022 academic year, a new quality management system for schools (QMS) was implemented for two years, in which QIBB was combined with the Quality Framework for General Education Schools. In accordance with changes in the quality assurance system, the legislative support for VET in Austria was also updated.